Eating disorder risk assessment and sociocultural attitudes toward body image among Polish and Turkish professional female football players - Staśkiewicz-Bartecka, Wiktoria; Aktaş, Samet; Zydek, Grzegorz; Kardas, Marek; Kałuża, Martyna; Michalczyk, Małgorzata Magdalena (Frontiers in Nutrition, 2024)
Introduction Football requires high physical fitness and often involves maintaining a specific physique, leading to harmful eating behaviors due to internal and external pressures. Cultural norms influence the prevalence and types of eating disorders (ED), with differences in eating habits, beauty standards, and socio-cultural pressures affecting ED development. This study assesses ED risk and analyzes socio-cultural attitudes toward body image among Polish and Turkish female football players. Methods The study was conducted from April to June 2024 and included 103 professional female football players aged 18–35 from Polish (n = 49) and Turkish (n = 54) clubs. Data were collected using the CAWI method via Google Forms. Participants completed EAT-26 and SATAQ-3 questionnaires, assessing ED risk and socio-cultural attitudes toward body image. Results 40.8% of participants were at risk for ED. No differences in ED prevalence were found between groups of different nationalities. Polish footballers at risk of ED scored higher on the Internalization-Pressure and Information subscales and the overall SATAQ-3 score. A weak but significant positive correlation was found between SATAQ-3 and EAT-26 scores. Discussion The study finds no nationality-based differences in ED prevalence among professional female football players, but ED is widespread, affecting about 40% of players. Nutritional status impacts ED risk, with higher risk among underweight and overweight players. Polish players are more influenced by socio-cultural standards of body image promoted by mass media. The study underscores the need for regular screening and psychological support.